Toxicidad aguda del extracto alcohólico e hidroalcohólico de hojas y corteza de Cecropia strigosa Trécul sobre nauplios de Artemia franciscana - Ferreyra Ushiñahua, Gilson Fabio (2025)
Cecropia strigosa Trecul is a plant with biomedical potential due to its phytochemical properties. However, its use in practical applications requires prior evaluation of its safety profile. Objective: to determine the acute toxicity of the alcoholic and hydroalcoholic extract of leaves and bark of Cecropia strigosa Trecul in nauplii of Artemia franciscana. Methodology: Leaves and bark of C. strigosa Trecul were collected from healthy individuals, following ethical and sustainability procedures. The plant materials were dried and finely ground for subsequent extraction. The alcoholic and hydroalcoholic extracts were prepared using analytical grade ethanol and distilled water. A. franciscana eggs were incubated in 3% Instant Ocean solution until reaching the nauplius phase, which were exposed to concentrations of 10, 100 and 1000 ppm of each extract for 24 hours. Nauplii mortality was recorded at intervals of 4, 8, 12 and 24 hours of exposure. The mean lethal concentration (LC50) for each extract was determined by appropriate statistical analyses. Results: The LC50 for both extracts (alcoholic and hydroalcoholic) was greater than 1000 ppm during the 24-hour exposure period. This indicates that C. strigosa Trécul extracts do not present acute toxicity in A. franciscana nauplii in the range of concentrations evaluated. Conclusion: the alcoholic and hydroalcoholic extracts of leaves and bark of C. strigosa Trecul do not present acute toxicity in nauplii of A. franciscana at the concentrations tested. This preliminary information contributes to the evaluation of the safety profile of this plant and its potential use in biomedical applications.